Kesadaran Penduduk Melaporkan Peristiwa Penting dan Peristiwa Kependudukan dan Implikasinya Terhadap Data Pemilih - Sitti Aminah (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
Problems of voter data becomes a crucial issue ahaead 2014 election. Purpose of this study is to describe the application of population regulation and implementation of e-KTP which has implications for the determination of the voter list. Data collection using Focus Group Discussion method in two step, the first step involved the experts and implementing agencies, and then second step involved Head of RT and village officials. Result of this study indicate that (1) awareness of the population in reporting important events and demographic events was low, due to social-economic factor, the ineffectiveness of socialization dan make citizenship documents if only need be. The suggestion are: (1) The awareness increasing of the populization is accompanied with the provision of easy access especially those with lower social and economic status and remote access form the public services. (2) Increase the role of RT/RW/Village Head appreciated by incentive for the achievement in the discipline of population administration in his region.